PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA PERAWAT PELAKSANA RUANG RAWAT INAP DI RUMAH SAKIT BETHESDA YOGYAKARTA - Sudarta, I Wayan (Jurnal Kesehatan, 2017)
Background:Nursing services in the hospital is one of the determinants factors of quality care. Nurses are not only responsible for the nursing implementations but also for a comprehensive patients care. Survey on the implementation of nursing care has shown a less accordance with the real implementation, and nurse job satisfaction survey has reported that 16.25% of them are not satisfied with their job. Methods:This study was using cross sectional approach population. 73 nurses with Diploma degree were included as respondents. The questionnaire, documentation, and observation were used in this study. Data analyzed with Logistic Regression. Results: In terms of motivation wald coefficient was 4,811 ( p=0,028 ) Discipline wald coefficient was 4.537, (p=0.033). Conclusion:Based on the result, there is an effect of discipline, on the nursing performance in terms of nursing care delivery.